Description and molecular phylogeny of Tethya leysae sp. nov. (Porifera, Demospongiae, Hadromerida) from the Canadian Northeast Pacific with remarks on the use of microtomography in sponge taxonomy - Heim, Isabel; Nickel, Michael (Zootaxa, 2010)
The sponge Tethya leysae sp. nov. (Porifera, Demospongiae, Hadromerida, Tethyidae) is a new species from the Canadian Northeast Pacific. Its type locality is the infralittoral around Ohiat Islet, Barkely Sound, Vancouver Island in Canada. Tethya leysae sp. nov. is a medium-sized spherical sponge with a verrucose surface, orange-yellow to light red alive and white with a greyish core in ethanol. The highly variable oxyspherasters (25-115 µm in size, R/C 0.34-0.69) are densely scattered almost throughout the entire cortex. The micrasters comprise acanthoxyspherasters, acanthostrongylasters, acanthotylasters and small oxyspherasters, which are present at low densities throughout the sponge and form a dense layer associated with the exopinacoderm. The megascleres and the auxiliary megascleres comprise oxeas and strongyloxeas. The new species is clearly distinguishable from the closely related T. californiana by the absence of spherules among the micrasters, the lack of an alveolar cortex and the extremely high density of megasters in the cortex. In addition, the R/C values of the megasters differ between the two species and the oxyspherasters of T. leysae sp. nov. rarely display bent rays. The morphological differences between the species are confirmed by nucleotide and amino acid substitutions within the cytochrome oxidase subunit I (COI) mtDNA gene. Phylogenetic analyses group T. leysae sp. nov. with T. californiana, T. actinia and T. minuta, which together form a sister group to a MediterraneanNorth Atlantic species cluster. Morphological analyses of the skeleton included x-ray microtomography (µCT) and virtual 3D reconstruction, which was used for the first time in conjunction with the description of a new sponge species. Microtomography permitted the visualization and analysis of spicules within the skeletal context or isolated in silico. The method represents a valuable extension to the sponge taxonomist’s toolbox since it allows morphometric measurements in 3D. µCT will thus supplement classical morphological methods such as light and scanning electron microscopy.